Neonatal Nicotine Exposure Primes Midbrain Neurons to a Dopaminergic Phenotype and Increases Adult Drug Consumption - Romoli, Benedetto; Lozada, Adrian F.; Sandoval, Ivette M.; Manfredsson, Fredric P.; Hnasko, Thomas S.; Berg, Darwin K.; Dulcis, Davide (Biological psychiatry (1969), 2019)
Nicotine intake induces addiction through neuroplasticity of the reward circuitry, altering the activity of dopaminergic neurons of the ventral tegmental area. Prior work demonstrated that altered circuit activity can change neurotransmitter expression in the developing and adult brain. Here we investigated the effects of neonatal nicotine exposure on the dopaminergic system and nicotine consumption in adulthood. Male and female mice were used for two-bottle-choice test, progressive ratio breakpoint test, immunohistochemistry, RNAscope, quantitative polymerase chain reaction, calcium imaging, and DREADD (designer receptor exclusively activated by designer drugs)-mediated chemogenic activation/inhibition experiments. Neonatal nicotine exposure potentiates drug preference in adult mice, induces alterations in calcium spike activity of midbrain neurons, and increases the number of dopamine-expressing neurons in the ventral tegmental area. Specifically, glutamatergic neurons are first primed to express transcription factor Nurr1, then acquire the dopaminergic phenotype following nicotine re-exposure in adulthood. Enhanced neuronal activity combined with Nurr1 expression is both necessary and sufficient for the nicotine-mediated neurotransmitter plasticity to occur. Our findings illuminate a new mechanism of neuroplasticity by which early nicotine exposure primes the reward system to display increased susceptibility to drug consumption in adulthood.